DEVELOPMENT OF RELATIONS WITH THE REPUBLIC OF TURKEY UNDER THE PRESIDENT OF THE REPUBLIC OF UZBEKISTAN SHAVKAT MIRZIYOYEV. (Ta'limning zamonaviy transformatsiyasi, 2024)
In this article, after the election of Shavkat Mirziyoyev to the post of the President of the Republic of Uzbekistan, the restoration of relations with the state of Turkey, development, strengthening of relations, and rapid growth in the directions of mutual relations are analyzed.В данной статье после избрания Шавката Мирзиёева Президентом Республики Узбекистан анализируется восстановление отношений с Турцией, развитие, укрепление связей, быстрый рост по направлениям взаимоотношений.Ushbu maqolada Shavkat Mirziyoyev O‘zbekiston Respublikasi Prezidenti lavozimiga saylangandan so‘ng Turkiya davlati bilan munosabatlarni qaytadan tiklanishi, rivojlanishi, aloqalarni mustahkamlanishi, o‘zaro munosabat yo‘nalishlarida ildam birlashib yuksalishlari tahlil etiladi.